2016
DOI: 10.2118/170942-pa
|View full text |Cite
|
Sign up to set email alerts
|

Foams Stabilized by In-Situ Surface-Activated Nanoparticles in Bulk and Porous Media

Abstract: Foams for subsurface applications are traditionally stabilized by surfactants. The goal of this work is to study foam stabilization by nanoparticles-in particular, by in-situ surface-hydrophobization of hydrophilic nanoparticles. The interfacial properties of the nanoparticles were modulated by the attachment of short-chain surface modifiers (alkyl gallates) that render them partially hydrophobic, but still fully dispersible in water. First, static foams were generated with nanoparticles with varying concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
3

Relationship

3
7

Authors

Journals

citations
Cited by 79 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…For the NP-stabilized foam, coalescence was not observed with the microscope, as stated above (see Figure and the Supporting Video). For a sufficient surface coverage by NPs (<30 nm) between two gas films, the coalescence is suppressed by a large maximum capillary pressure P c . , The high P c can be a major advantage for foam stabilization against coalescence with NPs ,, relative to surfactants. The resistance to coalescence increases when G s ′ > G s ″ as a solid-like elastic film is less prone to rupture, as observed in Figure C.…”
Section: Resultsmentioning
confidence: 99%
“…For the NP-stabilized foam, coalescence was not observed with the microscope, as stated above (see Figure and the Supporting Video). For a sufficient surface coverage by NPs (<30 nm) between two gas films, the coalescence is suppressed by a large maximum capillary pressure P c . , The high P c can be a major advantage for foam stabilization against coalescence with NPs ,, relative to surfactants. The resistance to coalescence increases when G s ′ > G s ″ as a solid-like elastic film is less prone to rupture, as observed in Figure C.…”
Section: Resultsmentioning
confidence: 99%
“…The external stimuli could be used to tune the self-assembly or aggregate structure, 37 vary the solubility, 24 trigger the crystallization of the surfactant, 38 modify foam film thickness, 22 trigger conformational changes, 30 or perform in situ surface modification. 17,39 Herein, we report a novel commercially available surfactant which exhibits a multistimuli-responsive behavior toward foam stabilization. The aforementioned second strategy was employed in this work where the foam stability was switched from a stable to an unstable state by tuning the interfacial behavior of self-assembled structures of the surfactant.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Jiang et al (2013) showed that bare silica nanoparticles, which were too hydrophilic to stabilize emulsions, could be hydrophobized in-situ by adsorption of trace amount of amidinium surfactant to stabilize octane-in-water Pickering emulsions. Recently, Singh and Mohanty (2015a) demonstrated that this concept could be applied in subsurface applications. They showed that in-situ surface-activated nanoparticles behave as surfactants and could potentially be used as foaming agents in gas enhanced oil recovery (EOR) processes.…”
Section: Introductionmentioning
confidence: 99%